Răspuns:
7+15:(-3)=7-5=2
(-8)+(-9):(+3)=(-8)+(-3)= -11
12-(-16):(-2)=12-8=4
-42-40:(-5)= -42+8= -34
17-(-20):10=17-(-2)=17+2=19
b)13+(-5-4):(+3)=13+(-9):(+3)=13-3=10
(-21)+(-8+23):(-5)=(-21)+15:(-5)=(-21)-3= -24
36-(6-12):(-2)=36-(-6):(-2)=36-3=33
-4-7:(-3-4)=-4-7:(-7)=-4+1= -3
8-(1-7):(-3+6)=8-(-6):3=8-(-2)=8+2=10
c) -8+(-12):4:(-1)=-8+(-3):(-1)= -8+3= -5
12+(-5+9):(-2)x3=12+4:(-2)x3=12-2x3=12-6=6
-5-(6-8)x8:(-3-1)=-5-(-2)x8:(-4)=5-(-16):(-4)=5-4=1
9-(-6+12):(-2-1)x(-5)=9-6:(-3)x(-5)=9+2x(-5)=9-10=-1
10-(-5-7):(4-10):(3-4)=10-(-12):(-6):(-1)=10-2:(-1)=10+2=12
Explicație pas cu pas: